2020
DOI: 10.32598/sija.10.15.3.1895.3
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Unilateral and Bilateral Electrical Stimulation of the Brain on Improving the Balance of the Elderly

Abstract: Objectives: This study aimed to investigate the effect of unilateral and bilateral electrical stimulation of the brain on balance in the elderly. Methods & Materials: Thirty-six elderly in Ilam City, Iran, participated in the study. In the pretest, the static balance was taken, and then the participants were randomly divided into three groups: unilateral brain stimulation, bilateral brain stimulation, and sham. The intervention took in 3 sessions. In the unilateral stimulation group, the anode electrode wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…When necessary, it activates pre-programmed motor patterns to respond to the body's position. In line with this theory, electrical stimulation in targeted areas, by engaging primary muscular zones and brain points integral to balance, can effectively enhance balance (18). Balance control necessitates the involvement of three information processing domains: visual, vestibular, and somatosensory senses, central integration within the brain, and motor response.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…When necessary, it activates pre-programmed motor patterns to respond to the body's position. In line with this theory, electrical stimulation in targeted areas, by engaging primary muscular zones and brain points integral to balance, can effectively enhance balance (18). Balance control necessitates the involvement of three information processing domains: visual, vestibular, and somatosensory senses, central integration within the brain, and motor response.…”
Section: Discussionmentioning
confidence: 94%
“…Additionally, Tapa et al ( 2022) assessed the impact of EMS combined with resistance exercises on physical and brain functions in middle-aged and elderly women. Their study reported significant improvements in walking speed, muscle strength, and balance tests after four weeks of intervention, suggesting that EMS in conjunction with resistance training is an effective approach to boost motor performance in this demographic (18).…”
Section: Discussionmentioning
confidence: 96%
“…This non-invasive stimulation can be given by either transcranial direct current stimulation (tDCS) or transcranial alternating current stimulation (tACS). In tDCS, the application of low-intensity (weak) and direct electric current is limited to the cortex, and the modification of electrode size can increase its low spatial focality to different areas of the cerebral cortex through the scalp influence on the neuron excitability (10), which can facilitate or inhibit the activity of the nerves (11,12). The after-effects of the stimulation, modulated by glutamatergic synapses, can result in long-term potentiation and depression-like mechanisms; however, the exact mechanism of action is still under investigation (13).…”
Section: Introductionmentioning
confidence: 99%